The enhancement of hospitality graduates' competency model for Malaysian higher education institutions - Roshita, Abdul Razak (2020)
Hospitality industry professionals agree that having the right competencies are essential components for hospitality graduates to succeed in the industry. However, hospitality education institutions have been blamed for providing out dated hospitality academic structure which are not equipping graduates with relevant competencies. This study therefore aims to develop a competency model for hospitality graduates through investigating the essential competencies required for the first line management level position in the hotel industry. This study used a qualitative approach, the Delphi method to identify and prioritize competencies thus further categorize them into competency clusters. This method involved three rounds of data collection with a panel of industry professionals from four and five star hotels in Peninsular Malaysia were invited as experts. A total of 32, 16 and 15 experts participated in the first round, the second round and the third round respectively. In the first round, findings revealed that from 69 competency items being forwarded, all competency items achieved above 50 percent responses indicating that all competency items were relevant. In the second round, panels indicated high level of agreement on 29 competency items with mean scores ranges from 4.06 to 4.69. The average level of agreement was recorded for 40 competency items with mean scores from 3.19 to 4.0. Finally, the third round saw a high level of consensus on the importance of competency items with the final lists of 69 competency items to cover 37 competency items under workplace cluster, 17 competency items were in personal effectiveness cluster, 12 competency items were in management cluster and three competency items were in academic cluster. The study indicated a need for coordinated efforts from educational providers and the industry professionals to prepare future hospitality graduates for the industry. The result could assist hospitality educators and higher education institutions offering Universiti Utara Malaysia hospitality programme in providing clear understanding of relevant competencies for hospitality graduates. This study also contributed to the body of literature on hospitality competencies in the local context.